Political Communication Brokerage and Election Law Compliance: The Role of Socio-Religious Values and Environmental Ethics in Tambak Lorok - Nugraheni Arumsari; Pawito; Andre Noevi Rahmanto; Didik Gunawan Suharto; Rizqi Adri Muhammad (Contemporary Issues on Interfaith Law and Society, 2026)
This study aims to examine the role of political brokers in communication practices in the Tambak Lorok fishing community in Semarang City, Central Java, focusing on compliance with election laws and the politicization of environmental issues. The community experiences multiple vulnerabilities, ranging from socio-ecological crises affecting socio-economic life to political mobilization practices that turn voting into an electoral commodity. Data were collected using a case study approach, specifically through in-depth interviews with 10 informants, including five brokers and five community members, as well as an analysis of secondary document sources. The results showed that three types of brokers, namely activists, clientelists, and opportunists, operated simultaneously, exploiting environmental issues, including tidal flooding, diesel fuel shortages, and coastal waste as political narratives. These narratives were used to build candidate legitimacy and mobilize votes based on promises of ecological solutions, often combined with the practice of money politics. Political brokers were not only agents of patronage but also communication actors who framed local issues in electoral political discourse. In practice, political brokers occupied a biased position by engaging in legitimate political communication and violating Law Number 7 of 2017. A central finding of this study is the systematic weaponization of Islamic jurisprudential concepts—specifically the intentional conflation of risywah (bribery) with shadaqah (alms) and hadiah (gifts)—within communal pengajian spaces to neutralize legal resistance to vote-buying. It constitutes a paradigmatic case of interfaith legal tension, where Islamic normative frameworks are inverted to subvert state electoral law. In conclusion, this study contributes to strengthening the understanding of informal actors, electoral law, and the quality of democracy, specifically at the local level, while expanding the discourse on how environmental issues are politicized in the context of urban coastal communities in developing countries.